A sociology of mental health and illness - Rogers, Anne (McGraw-Hill Open University Press, 2014)
How do we understand mental health problems in their social context? A former BMA Medical Book of the Year award winner, this book provides a sociological analysis of major areas of mental health and illness. The book considers contemporary and historical aspects of sociology, social psychiatry, policy and therapeutic law to help students develop an in-depth and critical approach to this complex subject. New developments for the fifth edition include: brand new chapter on prisons, criminal justice and mental health; expanded coverage of stigma, class and social networks; and updated material on the Mental Capacity Act, Mental Health Act and the Deprivation of Liberty. A classic in its field, this well established textbook offers a rich and well-crafted overview of mental health and illness unrivalled by competitors and is essential reading for students and professionals studying a range of medical sociology and health-related courses. It is also highly suitable for trainee mental health workers in the fields of social work, nursing, clinical psychology and psychiatry. -- Provided by publisher.